2019
DOI: 10.3389/fneur.2019.00246
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma von Willebrand Factor and Cellular Fibronectin in MRI-Defined Traumatic Microvascular Injury

Abstract: The neuropathology of traumatic brain injury (TB) is diverse, including primary injury to neurons, axons, glial cells, vascular structures, and secondary processes, such as edema and inflammation that vary between individual patients. Traumatic microvascular injury is an important endophenotype of TBI-related injury. We studied patients who sustained a TBI requiring ER evaluation and had an MRI performed within 48 h of injury. We classified patients into 3 groups based on their MRI findings: (1) those that had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Von Willebrand Factor (vWF), a concatemeric glycoprotein composed of 500‐kDa dimeric units, is synthesized within megakaryocytes and endothelial cells and functions as an integral mediator of both hemostasis and inflammation . In critical illness states, such as trauma, sepsis, and burns, sympathoadrenal activation and loss of the endothelial glycocalyx may instigate a shift toward a prothrombotic vascular endothelium, leading to large, swift increases in vWF, accompanied by concomitant decreases in the vWF cleaving protease, ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type‐1 repeats 13) . Much of the work that has previously focused on endotheliopathy of critical injury has targeted markers such as syndecan‐1, soluble thrombomodulin, and plasma adrenaline levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Von Willebrand Factor (vWF), a concatemeric glycoprotein composed of 500‐kDa dimeric units, is synthesized within megakaryocytes and endothelial cells and functions as an integral mediator of both hemostasis and inflammation . In critical illness states, such as trauma, sepsis, and burns, sympathoadrenal activation and loss of the endothelial glycocalyx may instigate a shift toward a prothrombotic vascular endothelium, leading to large, swift increases in vWF, accompanied by concomitant decreases in the vWF cleaving protease, ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type‐1 repeats 13) . Much of the work that has previously focused on endotheliopathy of critical injury has targeted markers such as syndecan‐1, soluble thrombomodulin, and plasma adrenaline levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent data have demonstrated that there is a sustained increase in vWF antigen, vWF activity, and proportion of high‐molecular‐weight vWF forms in the days following traumatic injury, suggesting movement toward a prothrombotic and proinflammatory phenotype within the circulation; furthermore, low ADAMTS13 levels have been linked to worse outcomes in these patients . While knowledge regarding the contribution of vWF to the development of TIC is rather limited, advances with respect to understanding TIC following traumatic brain injury (TBI) are highlighted later in this article and may provide insight into the role that vWF is playing …”
Section: Systemic Role Of Vwf In Coagulopathy and Inflammation Followmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI was used to separate patients into those with traumatic microvascular injury (TVI) defined as diffusion weighted MRI without frank hemorrhage, those with frank hemorrhage (TH) and those with no injury on MRI. NF-H was increased in both TH and TVI groups compared to MRI− group within the first 48 h following injury [25]. Importantly, NF-H plasma levels remained elevated after 48 h in the TVI group but not the TH group.…”
Section: Neurofilament Proteins (Nf-l; 3 Studies)mentioning
confidence: 82%
“…Impairment of the brain function results from a plethora of cerebrovascular events, including structural and functional dysfunction in cerebral hemodynamics. Cerebrovascular damage occurs in conditions such as stroke [9], cardiovascular [10] and neurodegenerative diseases [11], traumatic brain injury [12], and infectious diseases such as HIV [2] and cerebral malaria [5]. Cerebrovascular damage often involves obstruction of the BBB, which leads to its breakdown and impaired microcirculation.…”
Section: Introductionmentioning
confidence: 99%